Role of multi-parametric ultrasound in transient perivascular inflammation of the carotid artery syndrome. (May 2019) - Rafailidis, Vasileios; Chryssogonidis, Ioannis; Tegos, Thomas; Partovi, Sasan; Charitanti-Kouridou, Afroditi; Staub, Daniel
Introduction: The term "carotidynia" has been used to describe a symptom or a nosologic entity characterized by pain in the lateral neck region and over the carotid bifurcation. Recent advances in diagnostic imaging and the introduction of diagnostic criteria have led to the adoption of term "Transient perivascular inflammation of the carotid artery" (TIPIC) syndrome. Method: A retrospective analysis of the Radiology Department's database was performed to identify cases with the diagnosis of TIPIC syndrome. The purpose was to identify ultrasound images including B-mode technique, colour, power Doppler technique and contrast-enhanced ultrasound (CEUS). Findings: In total, five patients with the diagnosis of TIPIC syndrome are presented in this review. TIPIC syndrome is a clinic-radiologic entity characterized by pain over the carotid area, a symptom referring to a wide differential diagnosis where imaging plays a crucial role for proper diagnosis and treatment. Characteristic imaging findings on conventional ultrasound and CEUS are presented in this review. Discussion: TIPIC syndrome can be investigated with virtually any imaging modality. Ultrasound typically reveals perivascular infiltration and a hypoechoic intimal plaque, while no significant luminal narrowing is appreciated. Computed tomography angiography and magnetic resonance angiography also demonstrate these vascular wall changes primarily affecting the distal common carotid artery, the carotid bulb and possibly the internal carotid artery proximal part. Contrast enhancement is a very characteristic and constant finding of TIPIC lesions, suggestive of the inflammatory nature of the disease and can be appreciated on computed tomography angiography and magnetic resonance angiography. CEUS has been recently used and successfully observed contrast enhancement of the lesions, similar to computed tomography angiography and magnetic resonance angiography. Conclusion: Ultrasound remains the first-line modality for the evaluation of TIPIC syndrome, capable of providing all the information needed, especially if supplemented with the administration of microbubbles so that the enhancement of lesions can be evaluated.